A study of selected aspects of the University food service - Disini, Isabel Antonio 1939-
This study is part of the U.P. Development Staff research project entitled "Nutritional Status, Knowledge, Attitude, Practice (KAP) and Dietary Intake of U.P. Students with Emphasis on the Role of the University Food Service". The primary objective of this phase of the project was to study the foods served in the University Food Service (UFS) in terms of their acceptability, nutrient adequacy, reasonability of prices and sanitation standards, as well as the adequacy of facilities and equipment used. Eighteen food services units in the UFS constituted the samples. Data were gathered by means of questionnaires, interviews, food weighing, sanitation inspection checklists, swab tests, actual observations on cost considerations from planning to serving, examination of records and other written materials, costing of all ingredients used, measurement of plate waste and leftovers, and physical inventory of existing facilities and equipment. Findings indicated that the foods served in the UFS were deficient in quality and nutritional adequacy; there was laxity in cost control from planning to serving; dishwashing procedures dis not ensure cleanliness of dishes; sanitation, measured against the standards for food service establishments, was poor; and there was inadequacy of facilities and equipment. All these deficiencies were attributable to inefficient supervision and management.